FRI0279 Current Immunosuppressive Drugs Are Not Enough To Treat The Pulmonary Involvement of Connective Tissue Diseases. (15th July 2016) - Yazisiz, V.; Oygen, S.; Erbasan, F.; Arslan, G.; Gökalp, E.; Tazegül, G.; Avci, A.B.; Terzioğlu, E.
Abstract : Background: Interstitial lung diseases (ILDs) may occur secondary to connective tissue diseases (CTDs) and increase morbidity and mortality due to ventilation impairment. Objectives: To reveal clinical, laboratory and imaging features of CTD -ILDs and to analyze treatment approaches. Methods: One hundred thirty two consecutive patients were included in this cohort. Demographic characteristics, laboratory and HRCT results and treatment results were analyzed. More than 10% increase of pulmonary function tests were categorized as improvement, >10% decrease were categorized as deterioration and ±10% changes were categorized as stable disease. Results: There were 111 ILD patients (86.5% CTD-ILD) with follow-up time for more than 6 months. Median follow up time was 48 (Min-Max:6–260) months and mean age was 54.5±11.9 years. HRCT scan was repeated in median 3 (1–10) times per patients, with median 12.5 month intervals. The most frequent HRCT findings were ground-glass opacities, interlobular septal thickening and honeycomb patterns. 89.6% of CTD-ILD patients recieved corticosteroids and 44.8% recieved hydroxylchloroquine sulphate. Azathioprine and cyclophosphamide were the most common used immunosupresive drugs. Eighty four patients recieved at least one immunosuppressive agent. There were only 2 patients treated with four different immunosuppressive drugs. After treatment, mean pulmonary function tests did not significanty differ from baseline (p>0.05) (Table ). 35% of the patients improved forced vital capacity (FVC >%10 increase) by treatment whereas 31% had decreased and 34% were stable. Conclusions: It is not detected to have significant improvement by current immunosuppressive drugs in patients with CTD-ILDs. There is need more effective novel drugs to treat for CTD-ILD. Disclosure of Interest: None declared